Habitual sleep–wake behaviors and lifestyle as predictors of diurnal cortisol patterns in young breast cancer survivors: A longitudinal study. (March 2015) - Hsiao, Fei-Hsiu; Kuo, Wen-Hung; Jow, Guey-Mei; Chang, King-Jen; Yang, Po-Sheng; Lam, Hung-Bun; Lee, Jie-Jen; Huang, Chiun-Sheng; Liu, Yu-Fen; Lai, Yu-Ming
Highlights: A flatter diurnal cortisol pattern significantly predicted earlier mortality among metastatic breast cancer survivors. The main predictors of changes toward flatter diurnal cortisol patterns during the 8-month follow ups were greater tumor sizes, increases of BMI scores, and habitually later times of awakening among young breast cancer survivors. Besides the cancer's biological vulnerability, a healthy lifestyle including maintaining appropriate BMI and good sleep habits could be protective of positive cortisol regulation cancer. Summary: Objective: This study aimed to identify predictors of changes in diurnal cortisol patterns during the 8-month follow up period for young breast cancer survivors. Among the potential predictors were tumor size, lymph node metastasis, changes in sleep problems, habitual time of awakening and bedtime, physical activity levels, body mass index (BMI), and depressive levels across 8 months. Methods: The participants were 62 breast cancer women who were aged 40 years and below, and had completed active breast cancer treatment. The longitudinal data were collected at four points: baseline assessment ( T 0) and three follow-ups after baseline: T 1 (in the 2nd month), T 2 (in the 5th month), and T 3 (in the 8th month). The participants collected their salivary cortisol at home at six time points: upon waking, 30 and 45 min after waking, and at 1200 h, 1700 h, and 2100 h. They also completed several questionnaires: the Medical Outcomes Study Sleep scale; the Beck Depression Inventory-II, physical activity levels on a 10-point scale, time of going to bed, time of awakening, and total sleep hours. Results: This study found that the main predictors of changes toward flatter diurnal cortisol patterns during the 8-month follow ups were greater tumor sizes, increases of BMI scores, and habitually later times of awakening. Conclusions: While greater tumor sizes represent biological vulnerability of disruption of cortisol circadian rhythm, maintaining an appropriate BMI and good sleep habits could be a protective factor for normal cortisol regulation, which likely helps to reduce early mortality in young breast cancer survivors.